Mathematical Model for an Autonomous Vehicle to Fulfill the Closed Area - Kampanat Namngam; Pakkinee Chitsakul; Sutham Satthamsakul (My University, 2022)
This research presents the mathematical model to roam an autonomous vehicle in a closed region with minor coincident areas. This model is Blind Algorithm, no literature that concern on mathematical model. It is essential for agricultural technology, for example, shoveling soil for planting, spraying liquid fertilizer, harvesting agricultural products, to control the movement of the vehicle with the redundant path is as less as possible is benefited to decrease the working hours and also the burning oil and more for cost-saving without any expensive hardware. The almost wholly filled farmland depends on the shape, the size of the area, and the vehicle dimension.
Keywords: Robotic Path Planning Algorithms; Transportation and Mobility Innovations; Advanced Manufacturing and Logistics Optimization